Empowering Patients for Healthy Nutrition, Physical Activity, and Self-Care Using the Diabetes Score Questionnaire - Muhammad Jawad Hashim; Halla Mustafa (Dubai Diabetes and Endocrinology Journal)
Objectives: Lifestyle factors such as nutrition and physical activity play an important role in the management of diabetes mellitus. Unfortunately, adherence to lifestyle change remains low among patients with diabetes. The aim of this study was to evaluate the effectiveness of the Diabetes Score questionnaire in a clinical setting. Methods: The Diabetes Score is a 10-item shared decision-making tool designed to empower lifestyle change in individuals with diabetes. It yields an intuitive score from 0 to 100 based on a patient’s adherence to lifestyle recommendations. An observational study was conducted at an ambulatory health care center. After obtaining written informed consent, adult patients with type 2 diabetes mellitus were interviewed by a trained researcher using the Diabetes Score questionnaire. Patients’ Diabetes Score values were analyzed in reference to their glycemic control and other clinical and demographic factors. Results: A total of 60 individuals with type 2 diabetes participated in the study. The mean age was 56 years (minimum 43 years, maximum 70 years) with 60% being males. Higher Diabetes Scores correlated with better glycemic control (hemoglobin A1C; r = −0.23, p = 0.044) indicating the effect of lifestyle factors such as healthy nutrition, smaller portion sizes, active lifestyle, and aerobic exercise. The questionnaire showed internal consistency (alpha 0.66), construct validity, and high patient satisfaction (98%). Conclusion: Diabetes Score, a behavioral lifestyle questionnaire, correlates with glycemic control in type 2 diabetes. Diabetes Score can be used in clinical settings for measuring, discussing, and setting targets for lifestyle change among patients with diabetes.